2011
DOI: 10.1212/wnl.0b013e318228c136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complement and plasma cells in the brain of patients with anti-NMDAR encephalitis

Abstract: Complement-mediated mechanisms do not appear to play a substantial pathogenic role in anti-NMDAR encephalitis. In contrast, there are copious infiltrates of antibody-secreting cells (plasma cells/plasmablasts) in the CNS of these patients. The demonstration of these cells provides an explanation for the intrathecal synthesis of antibodies and has implications for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
249
4
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(278 citation statements)
references
References 10 publications
15
249
4
10
Order By: Relevance
“…Consistently, prominent CD138 + plasma cells could be detected in perivascular, and interstitial spaces of a biopsy specimen from another patient with anti‐NMDAR encephalitis (Fig. 1D) 6, 7…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Consistently, prominent CD138 + plasma cells could be detected in perivascular, and interstitial spaces of a biopsy specimen from another patient with anti‐NMDAR encephalitis (Fig. 1D) 6, 7…”
Section: Resultssupporting
confidence: 59%
“…Irrespective of the trigger of anti‐NMDAR encephalitis, data from previous studies suggested an enhancement of the immune response within the CNS, with potential antigen‐driven affinity maturation and clonal expansion of plasma cells 16. This hypothesis was suggested by three findings, (1) a frequent intrathecal synthesis of NMDAR antibodies even early in the disease course,1 (2) biopsy and autopsy material from patients showing brain inflammatory infiltrates containing plasma cells,6, 7 and (3) the better correlation of the course of the disease with CSF antibody titers than with serum antibody titers 5. All four treatment‐naive patients with recent onset anti‐NMDAR encephalitis in the current study showed intrathecal B‐cell and plasma cell accumulation and intrathecal production of NMDAR‐specific IgG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, known intrathecal synthesis of anti‐NMDAR antibody, pathologically confirmed by observing infiltration of antibody‐secreting cells in the CNS,28 indicate that plasma cells that translocate into the CNS space can evade attack from bortezomib, which had poor blood–brain barrier penetrance 29. Most specifically, long‐lived plasma cells that can survive several months to years7 may continuously secrete autoantibodies in the CNS.…”
Section: Discussionmentioning
confidence: 94%